Kinematic Analysis of Hitting: Launch Angle and Swing Velocity Differences in Elite vs. Amateur Softball Swing - Nur Rika Hasanah; Rusdiana, Agus; Hidayat, Iwa Ikhwan; Imanudin, Iman; Hardwis, Syam; Haryono, Tono (Journal of Sport Science and Fitness, 2024)
Hitting is a basic technique that must be mastered in softball. Efficient hitting requires good coordination between the lower limbs, core, and arms. This study aims to analyze the launch angle and exit velocity characteristics of the hitting technique between elite and amateur softball athletes. This study used a quantitative descriptive method. The population consisted of 13 athletes, including 5 elite athletes and 8 amateur athletes, who were selected using purposive sampling. Data collection used documentation techniques by recording the batting movements of the samples which then the video results will be analyzed using Kinovea and SkillSpector software, and the data was analyzed using SPSS version 26.0 with Independent Sample T-Test. The results showed significant differences in launch angle (p=0.025), exit velocity (p=0.004), and swing speed (p=0.015) between elite and amateur athletes. However, there were no differences in elbow angle (p=0.904) and elbow velocity (p=0.123). This study concludes that there are significant differences in batting technique characteristics between elite and amateur softball athletes, with elite athletes showing better performance in launch angle, exit velocity, and swing speed. However, both samples were similar in elbow and elbow angle velocity.